Perspektiven für die Logikprogrammierung - Kleine Büning, Hans; Lettmann, Theodor (Workshop Wissensrepräsentation in Expertensystemen)

Historiographie wissenschaftlicher Disziplinen als Kombination von Problem- und Sozialgeschichtsschreibung: Formale Logik im Deutschland des ausgehenden 19. Jahrhunderts - Peckhaus, Volker (Die geschichtliche Perspektive in den Disziplinen der Wissenschaftsforschung. Kolloquium an der TU Berlin, Oktober 1988. Mit Beiträgen von Michael Heidelberger, Walter Kaiser, C. Ulises Moulines, Volker Peckhaus, Wolf Schäfer, Burghard Weiss)

Die Johanneskirche am Feuersee in Stuttgart und der Architekt Christian Friedrich von Leins (1814 - 1892), Magisterarbeit masch. - Seng, Eva- Maria

„Wenn man die Augen hätte schließen und schlafen können...“. Zu Arno Schmidts Nachkriegsroman „Brand’s Haide“ - Eke, Norbert Otto (Arno Schmidt. Das Frühwerk II. Romane. Interpretationen von ‚Brand’s Haide’ bis ‚Gelehrtenrepublik’)

A Highly Integrated Tool Set for Program Development Support - Engels, Gregor; Janning, Thorsten; Schäfer, Wilhelm (Proceedings of the conference on ACM SIGSMALL/PC symposium on ACTES (SIGSMALL 1988), Cannes (France))
This paper describes the design of the integrated user interface of the software development environment IPSEN (Integrated Programming Support Environment). We explain the characteristic features of the IPSEN user interface, namely the structured layout of the screen, the command-driven tool activation, and especially the highly integrated use of the IPSEN tool set. We demonstrate those features by taking a sample set of tools of the IPSEN environment. That tool set supports all the programming-in-the-small activities within IPSEN. Finally, we sketch the realization of two prototypes running on an IBM-AT and a net of SUN workstations.

Konzeption einer integrierten Datenbank-Entwurfsumgebung - Engels, Gregor; Hohenstein, Uwe; Neugebauer, Leonore; Saake, Gunter; Ehrich, Hans-Dietrich (Proceedings of DBTA/SI Data Dictionaries und Entwicklungswerkzeuge für Datenbank-Anwendungen, Zürich, Switzerland)

Auf dem Weg zu einer integrierten Datenbank-Entwurfsumgebung - Engels, Gregor; Hohenstein, Uwe; Saake, Gunter; Ehrich, Hans-Dietrich (Proceedings of the GI-Workshop on "Sprachspezifische Programmierumgebungen")

Ein Konzept zur Beschreibung von Software-Architekturen - Ebert, Jürgen; Engels, Gregor

Die Benutzerschnittstelle einer integrierten Modula-2 Programmentwicklungsumgebung - Engels, Gregor; Janning, Thorsten; Schäfer, Wilhelm (Proceedings of GI-Workshop Sprachspezifische Programmierumgebungen, Darmstadt, Germany)

On the limits of computations with the floor function - Babai, László; Just, Bettina; Meyer auf der Heide, Friedhelm (Information and Computation)

Fast algorithms for N-dimensional restrictions of hard problems - Meyer auf der Heide, Friedhelm (Journal of the ACM (JACM))

A tradeoff between search and update time for the implicit dictionary problem - Borodin, Allan; Fich, Faith E.; Meyer auf der Heide, Friedhelm; Upfal, Eli; Wigderson, Avi (Theoretical Computer Science)

Dynamic perfect hashing: upper and lower bounds - Dietzfelbinger, M.; Karlin, A.; Mehlhorn, K.; Meyer auf der Heide, Friedhelm; Rohnert, H.; Tarjan, R.E. ([Proceedings 1988] 29th Annual Symposium on Foundations of Computer Science)

On computations with integer division - Just, Bettina; Mathematik, Fb; Meyer auf der Heide, Friedhelm; Informatik, Fb; Wigderson, Avi (STACS 88)

Upper and lower bounds for the dictionary problem - Dietzfelbinger, M.; Mehlhorn, K.; Meyer auf der Heide, Friedhelm; Rohnert, H. (SWAT 88)

Enhancement Techniques in Digital Image Processing - Domik, Gitta (Proceedings of the Computer Science Symposium)

A Comparison of Coherent and Differentially Coherent Detection Schemes for Fading Channels - Haeb-Umbach, Reinhold (International Conference on Vehicular Technology, Philadelphia)
The common basis of coherent and differentially coherent detection is considered from the viewpoint of carrier recovery as the estimation of fading distortion. In the differentially coherent receiver a simple estimate of the fading distortion is used whereas the coherent receiver uses the optimal estimate. The bit error rates (BERs) for M-ary PSK (phase-shift keyed) and DPSK (double phase-shift keyed) transmission are calculated using a single method of calculation for both detection schemes. The calculation takes into account nonperfect carrier recovery, cochannel interference, and diversity. The results allow a direct comparison of the two schemes and show that coherent detection is preferable in many realistic fading environments.

A digital Synchronizer for Linearly Modulated Signals Transmitted over a Frequency-Nonselective Fading Channel - Haeb-Umbach, Reinhold; Meyr, Heinrich (International Conference on Communications, Philadelphia)
A digital carrier recovery structure which allows coherent detection on frequency-nonselective fading channels is presented. The synchronizer estimates the multiplicative distortion introduced by the channel. It is shown that the structure is superior to a phase-locked loop and is well suited for a fully digital realization. A detailed synchronizer design and simulation results are presented for a land-mobile radio channel. This includes a novel scheme for a fully digital frequency offset estimation and correction.

A multi-spectral analysis system using large databases. - Brugel, Edward W; Domik, Gitta; Voels, Stephen A (European Southern Observatory Conference and Workshop Proceedings)

Dependence of image grey values on topography in SIR-B images - Domik, Gitta; Leberl, Franz; Cimino, J (International Journal of Remote Sensing)

SIR-B stereo-radargrammetry of Australia - Leberl, Franz; Mayr, W; Domik, Gitta; Kobrick, M (International journal of remote sensing)

Karl Eugen Müller (1865–1932) und seine Rolle in der Entwicklung der Algebra der Logik - Peckhaus, Volker (History and Philosophy of Logic)
Abstracts: The Philosopher's Index. Cumulative Edition 22 (1988), 509–510; Historical Abstracts 40A:4245. Rezensionen: Zbl. Math. 645.01019 (R. Murawski); MR 89e:01038 (Chris Brink).

Modellierung der dissipativen Eigenschaften linearer passiver Systeme unter Verwendung der Distributionentheorie - Böcker, Joachim

Generating Pattern Sequences for the Pseudo-Exhaustive Test of MOS-Circuits - Wunderlich, Hans-Joachim; Hellebrand, Sybille (18th International Symposium on Fault-Tolerant Computing, FTCS-18)

Integrated Tools for Automatic Design for Testability - Schmid, Detlef; Wunderlich, Hans-Joachim; Feldbusch, Fridtjof; Hellebrand, Sybille; Holzinger, Juergen; Kunzmann, Arno (Tool Integration and Design Environments, F.J. Rammig (Editor))

Automatisierung des Entwurfs vollständig testbarer Schaltungen - Hellebrand, Sybille; Wunderlich, Hans-Joachim (GI - 18. Jahrestagung II, Hamburg, 1988, Informatik-Fachberichte 188)

Magnetic-field-induced orientation of crystallites in powders of layered intercalation compounds detected by NMR - Halstead, Thomas K.; Schmidt, Claudia; Spiess, Hans W.; Schoellhorn, Robert; Mueller-Warmuth, Werner; Moeller, H. (The Journal of Physical Chemistry)
Keywords: Physical and Theoretical Chemistry; General Engineering

Deuteron two-dimensional exchange NMR in solids - Schmidt, Claudia; Blümich, B; Spiess, H.W (Journal of Magnetic Resonance (1969))
Keywords: General Engineering

Studium Arbeitslehre - Rückblick mit Ausblick - Bigga, Regine (Arbeitslehre / Polytechnik: Ein Beitrag zur Neuen Allgemeinbildung. Die Geschichte von Arbeit, Technik und Produktion im Unterricht)

Die Schleswig-Holsteinische Volkszeitung 1892 bis 1968 - Facetten aus ihrer Geschichte - Bigga, Regine; Danker, Uwe (Beirat für Geschichte der Arbeiterbewegung und Demokratie in Schleswig-Holstein)

Der VZ - Verlag in Photographien - Bigga, Regine; Danker, Uwe; Bruhn, Paul (Beirat für Geschichte der Arbeiterbewegung und Demokratie in Schleswig-Holstein)

INTEGRATED-OPTIC ROTATING WAVEPLATE FREQUENCY SHIFTER - Noé, Reinhold; SMITH, DA (ELECTRONICS LETTERS)

NEW FSK PHASE-DIVERSITY RECEIVER IN A 150 MBIT/S COHERENT OPTICAL-TRANSMISSION SYSTEM - Noé, Reinhold; SESSA, WB; WELTER, R; KAZOVSKY, LG (ELECTRONICS LETTERS)

ENDLESS POLARIZATION CONTROL-SYSTEMS FOR COHERENT OPTICS - Noé, Reinhold; HEIDRICH, H; HOFFMANN, D (JOURNAL OF LIGHTWAVE TECHNOLOGY)

INTEGRATED-OPTIC ROTATING WAVEPLATE FREQUENCY SHIFTER - Noé, Reinhold; SMITH, DA (ELECTRONICS LETTERS)

NEW FSK PHASE-DIVERSITY RECEIVER IN A 150 MBIT/S COHERENT OPTICAL-TRANSMISSION SYSTEM - Noé, Reinhold; SESSA, WB; WELTER, R; KAZOVSKY, LG (ELECTRONICS LETTERS)

ENDLESS POLARIZATION CONTROL-SYSTEMS FOR COHERENT OPTICS - Noé, Reinhold; HEIDRICH, H; HOFFMANN, D (JOURNAL OF LIGHTWAVE TECHNOLOGY)

AUTOMATIC ENDLESS POLARIZATION CONTROL WITH INTEGRATED-OPTICAL TI-LINBO3 POLARIZATION TRANSFORMERS - Noé, Reinhold; HEIDRICH, H; HOFFMANN, D (OPTICS LETTERS)

Blue phase liquid crystal system, method of operation and its use - Kitzerow, Heinz-Siegfried; Heppke, G.; Oestreicher, F.; Kitzerow, Heinz-Siegfried; Krumrey, M.

Electrooptic Effect in a Non-Polar Nematic Discotic Liquid Crystal - Heppke, G.; Kitzerow, Heinz-Siegfried; Oestreicher, F.; Quentel, S.; Ranft, A. (Molecular Crystals and Liquid Crystals Letters)

Rez.: Andreas Feige / Ingrid Lukatis / Wolfgang Lukatis: Kirchentag zwischen Kirche und Welt. Auf der Suche nach Antworten. Eine empirische Untersuchung auf dem 21. Deutschen Evangelischen Kirchentag Düsseldorf 1985 - Schroeter-Wittke, Harald (Der Evangelische Erzieher)

Schätze in irdenen Gefäßen - sind unsere neueren Tauflieder verwässert und vergeistigt? - Schroeter-Wittke, Harald (Der Evangelische Erzieher)

Spectrally Ordered Lie Algebras - Hilgert, Joachim (Group Theoretical Methods in Physics)

Invariant Lorentzian Orders on Simply Connected Lie Groups - Hilgert, Joachim (Arkiv för mat.)

Classification of Invariant Cones in Real Lie Algebras - Hilgert, Joachim; Hofmann, K.H. (Bull. AMS)

Invariant Cones in Lie Algebras - Hilgert, Joachim; Hofmann, K.H. (Semigroup Forum 37l. Semigroup Forum)